Benchmarking Lumbar Puncture Fluoroscopy Time during Fellowship Training - Yang, H. (AJNR Am J Neuroradiol, 2017)
We sought to establish a guide for identifying fellowship competency in performing fluoroscopically guided lumbar punctures. With a linear mixed-effects model, we compared the fluoroscopy time between the first and last 3 months of neuroradiology training. During 7 years, 55 fellows performed 1142 and 861 lumbar punctures in the first and last quarters of training. A target fluoroscopy time of 0.26 minutes, the upper 95% confidence interval, can serve as a fellowship benchmark for successfully achieving competence in fluoroscopically guided lumbar punctures.